Curriculum influence on interdisciplinary oral health education and practice. (28th March 2017) - Clark, Melinda; Quinonez, Rocio; Bowser, Jonathan; Silk, Hugh
Abstract: Objectives: Oral diseases are very prevalent across the lifespan and impact overall health, yet are largely preventable. The Smiles for Life (SFL) curriculum was created to educate healthcare providers about oral disease and support integration of oral health and primary care. This study examines SFL's influence on clinical practice and education. Methods: Surveys were sent to registered users of SFL. Users who self‐identified as direct care providers (DCPs), or educators, were included in the analysis. Results: Survey response rate was 18 percent, with 87 percent identifying as DCPs and 13 percent as educators. Across professions, 85 percent of DCPs reported SFL influencing their practice to some degree, with variance among profession type and experience. DCPs most commonly reported that SFL led them to improve how they conduct oral health activities, with 60 percent performing the activity more skillfully following completion of SFL. Fluoride varnish application was the most common practice behavior initiated, and caries risk assessments was the oral health activity affected to the greatest degree. A majority of educators (94 percent) reported that SFL led them to incorporate or enhance oral health in their teaching. SFL helped educators emphasize the importance of oral health, improved their ability to teach content, raised motivation, and reduced barriers to teaching oral health. Conclusions: Data supports that SFL is positively influencing oral health practice across professions, especially in areas of caries risk assessment and fluoride varnish application. SFL improves the frequency and quality with which DCPs and educators participate in oral health activities, and facilitates oral health inclusion in primary care.